If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5X + 4Y + z = 200 Solving 5X + 4Y + z = 200 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4Y' to each side of the equation. 5X + 4Y + -4Y + z = 200 + -4Y Combine like terms: 4Y + -4Y = 0 5X + 0 + z = 200 + -4Y 5X + z = 200 + -4Y Add '-1z' to each side of the equation. 5X + z + -1z = 200 + -4Y + -1z Combine like terms: z + -1z = 0 5X + 0 = 200 + -4Y + -1z 5X = 200 + -4Y + -1z Divide each side by '5'. X = 40 + -0.8Y + -0.2z Simplifying X = 40 + -0.8Y + -0.2z
| -4(x-5)+2=22 | | 9+(2x+5)=3(2x+4) | | 1.2+0.3x=0.5x-3.2 | | -9x^4=-48x^2+64 | | 0.5x-2+5= | | 14-7r=6-3r | | 19-3x=5x+3 | | 1x-2=-1 | | 2x-2=3x-1 | | 16x-10=6x+40 | | 5.4x-1=4.4x+9 | | (7/6)x+7=4 | | 16x+27=15x+18 | | 40-6x=4x | | 160+x=60 | | 7x+3(x+2)=-24 | | 8x+4y=254 | | 10x^2-(5/6)x-25=0 | | 9x+7=8x-8 | | 6x+27=11x+7 | | 2x^2-7x-39=0 | | 7x+11=11x+7 | | 7x+11=6x+27 | | 50=7x-6 | | 2(2-4x)=10-x | | 9-(2x+5)=3(2x+4) | | 8=x-13 | | x^3+14x=123 | | (4*4)+(r*r)=(r*r)*2*2 | | (4u^2)3/2 | | 3x+12=6x+3 | | m/-3+8=5 |